Pharmacological Aspects and Potential Use of Phloretin: A Systemic Review - Mariadoss, Arokia V.A.; Vinyagam, Ramachandran; Rajamanickam, Vinothkumar; Sankaran, Vijayalakshmi; Venkatesan, Sathish; David, Ernest (Mini Reviews in Medicinal Chemistry, 2019)
Over the past two decades, many researchers have concluded that a diet rich in polyphenolic compounds plays an important therapeutic role in reducing the risk of cancer, cardiovascular disease, inflammation, diabetes, and other degenerative diseases. Polyphenolic compounds have been reported to be involved in neutralization of reactive oxygen species and charged radicals, and have anticarcinogenic effects, hepatoprotective effects, low-glycaemic response, and other benefits. The benefits of fruits and vegetables may be partly attributable to polyphenolic compounds, which have antioxidant and free radical scavenging properties. Fruits such as apples contain a variety of phytochemicals, including (+)-catechin and (-)-epicatechin, phlorizin, phloretin quercetin, cyanidin-3-Ogalactoside, chlorogenic acid, and p-coumaric acid, all of which are strong antioxidants. Phloretin, a natural phenolic compound, is a dihydrochalcone, which is present in the apple. It exhibits a wide variety of activities such as antioxidative, anti-inflammatory, anti-microbial, anti-allergic, anticarcinogenic, anti-thrombotic, and hepatoprotective, besides being involved in the activation of apoptotic associated gene expression and signal transduction in molecular pathways. Despite a multitude of clinical studies, new efforts are needed in clinical research to determine the complete therapeutic potential of phloretin.
Keywords: Phloretin